Global magnitude and temporal trends of stroke attributable to lead exposure from 1990 to 2021 - Ying Wang; Ran Liu; Wenxia Li; PengNan Bao; JinWei Zhang; Wei Yue (Ecotoxicology and Environmental Safety)
Objective: Lead exposure is associated with an increased risk of stroke, but studies on the global burden of stroke attributable to lead exposure remain limited. This study evaluates the temporal and spatial trends in the disease burden of stroke and its three subtypes attributable to lead exposure in 204 countries and territories from 1990 to 2021. Methods: Data from Global Burden of Disease Study (GBD) 2021 were used to estimate annual deaths, disability-adjusted life years (DALYs), age-standardized mortality rate (ASMR), and age-standardized DALY rate (ASDR) of stroke attributable to lead exposure. The estimated annual percentage change (EAPC) was calculated to evaluate trends from 1990 to 2021. Results: Between 1990 and 2021, the global burden of stroke attributable to lead exposure increased significantly, with deaths rising from 341,294 to 556,595 and DALYs from 8.52 million to 12.02 million. However, ASMRs declined from 9.33 to 6.65 per 100,000 population (EAPC = −1.23), and ASDRs fell from 213.99 to 139.82 per 100,000 population (EAPC = −1.51). Among subtypes, ischemic stroke (IS) contributed the most to ASMRs, whereas intracerebral hemorrhage (ICH) accounted for the highest ASDRs. Males had higher ASMRs and ASDRs than females, although females exhibited greater reduction rates. The burden was disproportionately higher in older adults, particularly those over 70 years, with IS and ICH contributing significantly. Socio-demographic and regional disparities were evident, with low- and low-middle SDI regions bearing the highest burden. Conclusion: The stroke burden attributable to lead exposure remains high, with significant variations by age, sex, region, and subtypes. Public health measures and policies are urgently needed to prevent and mitigate lead exposure globally.